Comparative study on alkaloids and their anti-proliferative activities from three Zanthoxylum species - Yongqiang Tian; Chunyun Zhang; Mingquan Guo (BMC, 2017)
Abstract Background Alkaloids have been considered as the most promising bioactive ingredients in plant species from the genus Zanthoxylum. This study reports on the compositions and contents of the Zanthoxylum alkaloids (ZAs) from three Zanthoxylum species, and their potential anti-proliferation activities. Methods An HPLC-UV/ESI-MS/MS method was established and employed to analyze the alkaloids in different Zanthoxylum extracts. The common and unique peaks and their relative contents were summarized and compared to evaluate the similarity and dissimilarity of the three Zanthoxylum species. Meanwhile, inhibitory activity tests to four carcinoma cell lines, i.e., stomach tumor cells (SGC-7901), cervical tumor cells (Hela), colon tumor cells (HT-29) and Hepatic tumor cells (Hep G2), were carried out in vitro to evaluate the bioactivities of the ZAs. Results Seventy peaks were detected in the crude total alkaloid samples, and 58 of them were identified. As a result, 13 common peaks were found in the extracts of all the three Zanthoxylum species, while some unique peaks were also observed in specific species, with 17 peaks in Z. simulans, 15 peaks in Z. ailanthoides and 11 peaks in Z. chalybeum, respectively. The comparison of the composition and relative contents indicated that alkaloids of benzophenanthridine type commonly present in all the three Zanthoxylum species with high relative contents among the others, which are 60.52% in Z. ailanthoides, 30.52% in Z. simulans and 13.84% in Z. chalybeum, respectively. In terms of activity test, Most of the crude alkaloids extracts showed remarkable inhibitory activities against various tumor cells, and the inhibitory rates ranged from 60.71 to 93.63% at a concentration of 200 μg/mL. However, SGC-7901 cells seemed to be more sensitive to the ZAs than the other three cancer cells. Conclusion The alkaloid profiles detected in this work revealed significant differences in both structures and contents among Zanthoxylum species. The inhibitory rates for different cancer cells in this study indicated that the potential anti-cancer activity should be attributed to quaternary alkaloids in these three species, which will provide great guidance for further exploring this traditional medicinal resource as new healthcare products.